Changing the world thru da'wah - Yasin, Shaykh Khalid; One Islam Publications (N.S.W, Australia : One Islam Publications, 2006)
The misfortunes occuring to the Muslims is simply due to the fact that Muslims are moving away from the true teachings of Islam, as taught by Muhammad (peace be upon him). The world will be a better place if Islam is revived back into the Muslims' lives and ultimately, spread to the rest of the world
Title from title screen
Lecturer : Shaykh Khalid Yasin
Keywords: Da'wah (Islam); Islam -- Missions